Antiphospholipid antibodies in 57 children and adolescents with systemic lupus erythematosus - Campos, Lúcia Maria de Arruda; Kiss, Maria Helena B.; D'Amico, Élbio A.; Silva, Clóvis Artur Almeida (Revista do Hospital das Clínicas, 2003)
OBJECTIVE: To investigate the frequencies and behavior of antiphospholipid antibodies in 57 children and adolescents with systemic lupus erythematosus. METHODS: Anticardiolipin antibodies were investigated by ELISA and lupus anticoagulant antibodies by the international tests recommended. The antiphospholipid antibodies analyses were performed in frozen samples (mean of 5.3 samples per patient obtained during a mean follow-up period of 3 years and 7 months) and on blood samples collected between January 1997 and November 1998 (mean of 2.5 samples per patient during a 2-year follow-up period). RESULTS: The frequencies of antiphospholipid antibodies (anticardiolipin and lupus anticoagulant) were similar in the samples collected prospectively and in the frozen samples (retrospective study): 63.2% and 75.4% respectively. Positivity for these antibodies fluctuated during the follow-up period and was not associated with any clinical or laboratory parameters of lupus erythematosus, including autoantibodies and also including disease activity and/or severity scores. CONCLUSIONS: The frequencies of antiphospholipid antibodies in children and adolescents with lupus erythematosus were similar to those observed in adults. The positivity fluctuated during the follow-up and was not correlated with clinical and/or laboratory disease parameters.